Разработка новой технологии получения карбоната калия на Украине - Панасенко, Владимир Алексеевич; Гринь, Григорий Иванович; Семенов, Евгений Александрович; Очередко, Елена Анатольевна (Український державний хіміко-технологічний університет, 2006)
В работе рассмотрена разработка новой технологии получения карбоната калия в Украине из отечественного сырья.

The paper considers the development of a new technology for the production of potassium carbonate in Ukraine from domestic raw materials.
Development of a new technology for the production of potassium carbonate in Ukraine
Keywords: карбонат калия; potassium carbonate; калийное сырьё; potash raw materials; технология; technology